Knowledge and skills of basic emergency obstetrics care among healthcare providers in selected primary health care centres in Ibadan, Southwest Nigeria (2024)
Introduction: Healthcare providers (HCPs) need to be adequately informed and experienced in Basic Emergency Obstetric Care (BEmOC) techniques to effectively manage obstetric and neonatal emergencies. This study evaluated the knowledge and skills of HCPs in selected Primary Health Centres (PHCs) in Ibadan Metropolis, Nigeria. Method: This was a cross-sectional study comprising 319 HCPs working in 6 Local Government Areas within the Ibadan metropolis. A structured, self-administered questionnaire was used to collect data on their knowledge and skills regarding BEmOC. Both self-reported as well as demon-strated knowledge and skills were considered while comparisons were made among various HCPs. The knowledge scores were categorized as good (≥85.0%) and poor (<85.0%), and Skills as good (≥ 75th percentile) and poor (<75th percentile). Statistical analysis was done using Statistical Package for Social Sciences (25.0) with a p-value set at <5%. Results: The mean age of participants was 47.0±6.5 years with more than four-fifths, 261(81.8%), being Community Health Workers. Of all the partici-pants, 228(71.5%), have been practicing for over 10 years while only about one-quarter, 83(26.1%), had ever been trained on BEmOC. Among those ever trained, 45(54.2%) had the training within the last five years. Overall, only 1.3% and 1.8% of the participants demonstrated good knowledge and skills of BEmOC respectively. Both self-reported and standard scores were statistically similar regarding knowledge (p=0.54) and skills (p=0.08). There was no statistically significant difference between the level of education and knowledge of BEmOC, (aOR=0.52; 95% CI 0.26-1.05), but those in practice for more than 10 years were less likely to have good knowledge (aOR=0.54; 95% CI 0.45- 0.65). Conclusion: There is an urgent need for periodic training and re-training of HCPs especially at PHCs to improve their knowledge and skills of BEmOC to make a positive impact on improving maternal and neonatal outcomes.